On the obstacle problem for fractional semilinear wave equations. (September 2021) - Bonafini, M.; Le, V.P.C.; Novaga, M.; Orlandi, G.
Abstract: We prove existence of weak solutions to the obstacle problem for semilinear wave equations (including the fractional case) by using a suitable approximating scheme in the spirit of minimizing movements. This extends the results in Bonafini et al. (2019), where the linear case was treated. In addition, we deduce some compactness properties of concentration sets (e.g. moving interfaces) when dealing with singular limits of certain nonlinear wave equations.